If we plug in n = 1, we get:
a1 = -7(1) - 5 = -7 - 5 = -12
If we plug in n = 2, we get:
a2 = -7(2) - 5 = -14 - 5 = -19
If we plug in n = 3, we get:
a3 = -7(3) - 5 = -21 - 5 = -26
If we plug in n = 4, we get:
a4 = -7(4) - 5 = -28 - 5 = -33
Therefore, the first four terms of the sequence are: -12, -19, -26, -33.
Find the first four terms of the sequence defined below, where n represents the position of a term in the sequence. Start with n = 1.
an = –7n − 5
first four terms
5 answers
Find the first four terms of the sequence defined below, where n represents the position of a term in the sequence. Start with n = 1.
an = 2(3)n
first four terms
an = 2(3)n
first four terms
If we plug in n = 1, we get:
a1 = 2(3)(1) = 6
If we plug in n = 2, we get:
a2 = 2(3)(2) = 12
If we plug in n = 3, we get:
a3 = 2(3)(3) = 18
If we plug in n = 4, we get:
a4 = 2(3)(4) = 24
Therefore, the first four terms of the sequence are: 6, 12, 18, 24.
a1 = 2(3)(1) = 6
If we plug in n = 2, we get:
a2 = 2(3)(2) = 12
If we plug in n = 3, we get:
a3 = 2(3)(3) = 18
If we plug in n = 4, we get:
a4 = 2(3)(4) = 24
Therefore, the first four terms of the sequence are: 6, 12, 18, 24.
Find the first four terms of the sequence defined below, where n represents the position of a term in the sequence. Start with n = 1.
an = 3(2)n
an = 3(2)n
If we plug in n = 1, we get:
a1 = 3(2)(1) = 6
If we plug in n = 2, we get:
a2 = 3(2)(2) = 12
If we plug in n = 3, we get:
a3 = 3(2)(3) = 18
If we plug in n = 4, we get:
a4 = 3(2)(4) = 24
Therefore, the first four terms of the sequence are: 6, 12, 18, 24.
a1 = 3(2)(1) = 6
If we plug in n = 2, we get:
a2 = 3(2)(2) = 12
If we plug in n = 3, we get:
a3 = 3(2)(3) = 18
If we plug in n = 4, we get:
a4 = 3(2)(4) = 24
Therefore, the first four terms of the sequence are: 6, 12, 18, 24.